Dosimetric studies of cadmium free alloy used in compensator based intensity modulated radiotherapy. (October 2017) - Kaushik, Sandeep; Punia, Rajesh; Tyagi, Atul; Singh, Mann P.
Abstract: Aim of this study was to investigate dosimetric properties of cadmium free alloy which is used in compensator based intensity modulated radiotherapy (cIMRT). A mixture of lead, bismuth and tin was used to prepare the alloy whose melting point is 90–95 °C. Slabs of different thicknesses ranging from 0.71 cm to 6.14 cm were prepared. Density of alloy was measured by Archimedes' principle using water. For six megavolt (6 MV) photon beam energy transmission, linear effective attenuation coefficient (µeff ), tissue phantom ratio ( TPR 10 20 ), beam hardening, surface dose (Ds ), percentage depth dose (PDD) and effect of scatter has been measured and analyzed for different field sizes and different thickness of compensator. Effect of extended source to detector distance (SDD) on transmissions and µeff was measured. The density of alloy was found to be 9.5456 g/cm 3 . At SDD of 100 cm, µeff was observed 0.4253 cm −1 for a field size of 10×10 cm 2 . Calculated TPR 10 20 was found to be within 3% of experimental TPR 10 20 . It was found to be increasing with increasing thickness of compensator. Ds was found to decrease with thickness of compensator and increase with wider collimator opening due to increased scattered dose. Compensator slabs of 1 cm, 1.98 cm and 4.16 cm decreased surface dose by 4.2%, 6.1% and 9.5% respectively for a field size of 10×10 cm 2 at 100 cm SDD. For small field size of 3×3 cm 2 and 5×5 cm 2 PDDs are increased from 3.0% to 5.5% of open beam PDDs as compensator thickness increased from 1 cm to 6.14 cm at a depth of 10 cm in water while variation in PDD is insignificant in for larger field sizes 10×10 cm 2 to 20×20 cm 2 . A high degree of intensity modulation is essential in cIMRT and it can be achieved with this compensator material. Dosimetric properties analyzed in this study establish this alloy as a reliable, reusable, optimally dense and cost effective compensator material. Highlights: Alloy of lead, tin and bismuth was prepared and found reliable, reusable, optimally dense and cost effective for compensator based intensity modulated radiotherapy. Transmission data measured and validated. Beam hardening quantified. Effect of scattered photons has been explained. Measured effective attenuation coefficient is optimum for intensity modulation.